EMOTIONAL INTELLIGENCE AMONG FEMALE BASEBALL PLAYERS: A PSYCHOLOGICAL PROBE - Singh Dalwinder; Dureja Gaurav; Dr. Dolly (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : The present study was conducted to determine the emotional intelligence among Indian female baseball players. Material : For the purpose of present study, two hundred (N=200) senior national female baseball players were selected through purposive sampling technique from different regions of India. They were selected from four different regions: A (North region baseball players=50), B (East region baseball players=50), C (West region baseball players=50) and D (South region baseball players=50). To collect the required data for the present study, the questionnaire developed by Hyde et al. (2001) on emotional intelligence was administered. One Way Analysis of Variance (ANOVA) was employed to compare the entire regions. Where 'F' values were found significant, LSD (Least Significant Difference) Post-hoc test was applied to find out the direction and degree of difference. The level of significance was set at 0.05. Results : Significant differences were observed among North, East, West and South regions female baseball players on the sub-parameters; empathy, self-development, value orientation and on the parameter Emotional Intelligence (Total). No significant differences were noticed on the sub-parameters; self-awareness, self-motivation, emotional stability, managing relations, integrity, commitment and altruistic behaviour. Conclusion: The outcome of results might be due to the fact that East region female baseball players are able to pay attention to the worries and concerns of others, can listen to someone without the urge to say something, can stay focused under pressure, are able to handle multiple demands and able to identify and separate their emotions.